Impact of Social Media Reels On Impulse Buying Among Young Consumers.” - Sripathi, Dr. Madhavi; B. Naga Siddhardha; B. Naga Siddhardha; Sk. Meraaj Shareef; S. Venkata (Journal of Advanced Research in Journalism & Mass Communication, 2025)
Social media has evolved beyond communication into a powerful marketing platform, with short-form videos [2] (reels) becoming increasingly influential. This research paper investigates the impact of social media reels on impulse buying [4] behaviour among today’s young adults. Using a structured questionnaire, responses were gathered from 100 active social media users aged 18–25. The research identifies visual appeal [3], influencer [5] promotion, emotional engagement, and limited-time offers as key triggers for spontaneous buying decisions. Findings reveal that 68% of participants admitted to making at least one unplanned purchase after watching reels. Statistical analysis suggests a significant positive correlation between reel engagement and impulse buying [4] tendency. The study provides actionable insights for marketers to design effective digital campaigns while highlighting the importance of consumer awareness to mitigate impulsive purchasing.